Anisotropic Diffusion of e± in Pulsar Halos over Multiple Coherence of Magnetic Fields - Kai Yan; Sha Wu; Ruo-Yu Liu (The Astrophysical Journal)
The slow particle diffusion in pulsar halos, inferred from TeV gamma-ray surface brightness profiles (SBPs), is attributed to cross-field diffusion under the anisotropic diffusion model. This model assumes sub-Alfvénic interstellar turbulence in the medium surrounding the pulsar and a rough alignment of the line of sight of observers toward the pulsar with the local mean magnetic field direction in the halo. In this model, the expected morphology of a pulsar halo is highly dependent on the properties of the interstellar magnetic field. We investigate the anisotropic diffusion of electron–positron pairs across multiple coherence of magnetic fields in pulsar halos in this work. We focus particularly on their influence on the predicted gamma-ray SBP and the asymmetry of the halo’s morphology, as well as the observational expectations of the Large High Altitude Air Shower Observatory. Our results indicate that the requirement of a specific magnetic field geometry can be alleviated when accounting for a limited (and realistic) coherence length of the magnetic field in the model. Also, the halo’s morphology may appear less asymmetric, especially after being smoothed by the point-spread function of instruments. This largely relaxes the tension between the asymmetric morphology of halos predicted by the model and the lack of apparent asymmetric halos detected so far. Our findings demonstrate the important influence of the coherence length of the interstellar magnetic field on the distribution of particles around their accelerators, and the consequence for the measured source morphology.